Findings of the Association for Computational Linguistics: ACL-IJCNLP 2021 2021
DOI: 10.18653/v1/2021.findings-acl.429
|View full text |Cite
|
Sign up to set email alerts
|

John praised Mary because _he_? Implicit Causality Bias and Its Interaction with Explicit Cues in LMs

Abstract: Some interpersonal verbs can implicitly attribute causality to either their subject or their object and are therefore said to carry an implicit causality (IC) bias. Through this bias, causal links can be inferred from a narrative, aiding language comprehension. We investigate whether pre-trained language models (PLMs) encode IC bias and use it at inference time. We find that to be the case, albeit to different degrees, for three distinct PLM architectures. However, causes do not always need to be implicit-when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Overall, the performance varies across different models, decoding procedures, and bias types. However, in general, the models are more likely to capture the object bias, as can be noted by the (almost) overall higher CS values for the ES verbs, aligning with results from, for example, Kementchedjhieva et al, 2021 andZarrieß et al, 2022 which as well point towards a general tendency of LLMs to establish coreference to the object. Moreover, it is noticeable that for each decoding procedure the ability to capture the IC bias of SE verbs tends to improve when prompts are augmented with adverbial modifiers.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Overall, the performance varies across different models, decoding procedures, and bias types. However, in general, the models are more likely to capture the object bias, as can be noted by the (almost) overall higher CS values for the ES verbs, aligning with results from, for example, Kementchedjhieva et al, 2021 andZarrieß et al, 2022 which as well point towards a general tendency of LLMs to establish coreference to the object. Moreover, it is noticeable that for each decoding procedure the ability to capture the IC bias of SE verbs tends to improve when prompts are augmented with adverbial modifiers.…”
Section: Resultssupporting
confidence: 83%
“…And, as several psycholinguistic studies have demonstrated that the IC bias is not only highly reliable but also robust across different languages (Ferstl et al, 2011;Goikoetxea et al, 2008;Hartshorne et al, 2013;Bott and Solstad, 2014), it has become an an intriguing domain for testing language models. Earlier studies, including those conducted by Upadhye et al, 2020, Davis and van Schijndel, 2020, Kementchedjhieva et al, 2021and Zarrieß et al, 2022, have examined the performance of LLMs in capturing the IC coreference bias. I.e., they concentrated on single-word prediction tasks and evaluated the models' ability to generate continuations of such classic prompts, like examples (1) and (2), and predominantly found that LLMs display limited ability to systematically incorporate the IC coreference bias in their genera-tions.…”
Section: Implicit Causalitymentioning
confidence: 99%
See 1 more Smart Citation
“…1 Within work in natural language processing, existing models have been claimed to capture aspects of Principle A (e.g., Warstadt et al, 2020;Hu et al, 2020). Principle C has received less attention, though see Mitchell et al (2019) which found that LSTM language models failed to obey Principle C. Coreference, more broadly, has also been explored, with results suggesting that models encode features of coreference resolution (e.g., Sorodoc et al, 2020) and the interaction of implicit causality and pronouns (verb biases that influence preferred antecedents for pronouns; Upadhye et al, 2020;Davis and van Schijndel, 2021;Kementchedjhieva et al, 2021).…”
Section: Introductionmentioning
confidence: 99%